Hydrogel Films Derived Water Hyacinth Stems And Banana Peels Pectin: Tensile Performance And Swelling Ability - Retno Febriyanti; Muthia Elma; Iryanti Fatyasari Nata; Ni Kadek Devi Ananda Saraswati; Paskah Fransiska Afrida Simatupang (Faculty of Science and Technology Universitas Islam Negeri Ar-Raniry, 2023)
Abstract: Hydrogel films are sheet materials that form a 3D network structure and can be fabricated from one or more constituent materials. A combination of two natural polymers, namely carboxymethyl cellulose (CMC) derived from water hyacinth stems (WHS) and banana peel pectin, constructs these hydrogel films that are used as coating materials for food packaging. Citric acid replenishment to stabilize the cross-linking of the hydrogel films. This study is intended to determine the effect of WHSCMC, pectin, and citric acid on the swelling abilities and tensile performances of hydrogel films. CMC synthesis begins with harvesting water hyacinth stems obtained from the Gambut area waters in South Kalimantan, Indonesia. Then carried out the extraction and bleaching processes of cellulose. Cellulose extract powder was processed in two stages, videlicet alkalization and carboxymethylation, to obtain cellulose derivatives in the form of CMC. The results of WHSCMC were analyzed using FT-IR (Fourier Transform Infra-Red) and compared with commercial CMC. Giving results with significant similarity at the peaks of 998 cm-1 and 1015 cm-1, specifically the ether glycosidic group. Fabrication of hydrogel films combines WHSCMC and banana peel pectin with various compositions (100:0, 90:10, 70:30, and 50:50 wt.%) with added citric acid as an aid for crosslinking at various concentrations (5, 10, and 15 wt.%). Hydrogel films sample 70:30, 5 wt.% (CPc-5) gave optimum results from the characterization of hydrogel films related to food packaging application coatings in the form of swelling ability of 6,647 g/g, tensile strength of 11,770 MPa, and elongation test of 11,896%. FT-IR analysis of CPc-5 indicates that there are carboxyl groups (COO-) and hydroxyl groups (-OH), which play a role in the formation of cross-links and hydrophilic properties.Abstrak: Film hidrogel merupakan material lembaran yang membentuk struktur jaringan 3D dan dapat dibuat dari satu atau lebih bahan penyusun. Kombinasi dua polimer alami, yaitu karboksimetil selulosa (CMC) yang berasal dari batang eceng gondok (BEG) dan pektin kulit pisang membentuk film hidrogel yang digunakan sebagai bahan pelapis kemasan makanan. Penambahan asam sitrat untuk menstabilkan ikatan silang film hidrogel. Penelitian ini bertujuan untuk mengetahui pengaruh CMC BEG, pektin, dan asam sitrat terhadap kemampuan pembengkakan dan kinerja kekuatan tarik film hidrogel. Sintesis CMC diawali dengan pemanenan batang eceng gondok yang diperoleh dari perairan daerah Gambut, Kalimantan Selatan-Indonesia. Kemudian dilakukan proses ekstraksi dan pemutihan selulosa. Serbuk ekstrak selulosa diproses dalam dua tahap yaitu alkalisasi dan karboksimetilasi untuk mendapatkan turunan selulosa berupa CMC. Hasil CMC BEG dianalisis menggunakan FT-IR (Fourier Transform Infra-Red) dan dibandingkan dengan CMC komersial. Hasil yang diperoleh adalah adanya kemiripan pada puncak 998 cm-1 dan 1015 cm-1, yaitu gugus eter glikosidik. Pembuatan film hidrogel mengkombinasikan CMC BEG dan pektin kulit pisang dengan berbagai komposisi (100:0, 90:10, 70:30, dan 50:50 % berat) dengan penambahan asam sitrat sebagai pengikat silang dengan berbagai konsentrasi (5, 10, dan 15 % berat). Sampel film hidrogel 70:30, 5% (CPc-5) memberikan hasil optimum dari karakterisasi film hidrogel terkait pelapis aplikasi kemasan makanan berupa uji kemampuan pembengkakan sebesar 6,647 g/g, kuat tarik 11,770 MPa, dan elongasi sebesar 11,896%. Analisis FT-IR terhadap CPc-5 menunjukkan adanya gugus karboksil (COO-) dan gugus hidroksil (-OH) yang berperan dalam pembentukan ikatan silang dan sifat hidrofilik.